Influence of substituents and functional groups on the surface composition of ionic liquids - Kolbeck, Claudia; Niedermaier, Inga; Deyko, Alexey; Lovelock, Kevin; Taccardi, Nicola; Wei, Wei; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2014)
We have performed a systematic study addressing the surface behavior of a variety of functionalized and non-functionalized ionic liquids (ILs). From angle-resolved X-ray photoelectron spectroscopy, detailed conclusions on the surface enrichment of the functional groups and the molecular orientation of the cations and anions is derived. The systems include imidazolium-based ILs methylated at the C2 position, a phenyl-functionalized IL, an alkoxysilane-functionalized IL, halo-functionalized ILs, thioether- functionalized ILs, and amine-functionalized ILs. The results are compared with the results for corresponding non-functionalized ILs where available. Generally, enrichment of the functional group at the surface is only observed for systems that have very weak interaction between the functional group and the ionic head groups. Scratching the surface: The surface behavior of various functionalized ionic liquids (ILs) is studied by angle-resolved X-ray photoelectron spectroscopy and conclusions on surface-enrichment effects and molecular orientation of cations and anions are derived (see figure; Im=imidazolium, Tf=trifluoromethanesulfonyl). Overall, surface enrichment is only observed for functional groups that interact weakly with the ionic head groups. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Transition of TiO2 nanotubes to nanopores for electrolytes with very low water contents - Wei, Wei; Hauser, Christina; Wei, Wei; Berger, Steffen; Hauser, Christina; Meyer, Karsten; Yang, Mingjun; Schmuki, Patrik (Electrochemistry Communications, 2010)
Over the past decade, the electrochemical formation of self-organized nanotube layers in dilute fluoride containing electrolytes has been studied intensively. In the present work, we show that by anodization of Ti in similar electrolytes but containing only very low water contents, the formation of ordered TiO nanoporous structures can be observed. I.e., the water content in the electrolyte is the critical factor that decides whether self-ordered oxide tubes or pores are formed. This supports the concept that tube formation originates from ordered porous oxide by a "pore-wall- splitting" mechanism. © 2010 Elsevier B.V. All rights reserved.

Zwitterionic clusters with dianion core produced by electrospray ionisation of Brønsted acidic ionic liquids - Li, Jing; Nye, Leanne; Schulz, Peter; Wasserscheid, Peter; Ivanovic-Burmazovic, Ivana; Drewello, Thomas; Wei, Wei (Physical Chemistry Chemical Physics, 2012)
New Brønsted acidic ionic liquids (BAILs) are prepared by treating zwitterions, which are composed of an imidazolium cation and a sulfonate anion, with an alkanedisulfonic acid. Acidification of the zwitterions produces the cation and deprotonation of the alkanedisulfonic acid forms the anion of the new BAILs. Direct laser desorption/ionisation (LDI), matrix-assisted LDI (MALDI) and electrospray ionisation (ESI) are employed to transfer ions into the gas-phase for detection by mass spectrometry and for dissociation studies by tandem mass spectrometry. The components of the BAILs are confirmed by LDI and MALDI by the detection of the respective cation and anion and by ESI by the observation of the cation and the dianion. A prominent feature of ESI is the formation of aggregates (cluster ions). Positively charged cluster ions are formally composed of multiple zwitterions plus one additional proton. In the negative-ion mode the clusters also incorporate the zwitterions which are, however, linked with the alkanedisulfonate dianion. In collision-induced dissociations (CID), the cationic aggregates show the evaporation of zwitterions until the protonated zwitterion is reached. Similarly, the cluster dianions release zwitterions until the free alkane disulfonate dianion is reached. However, the 1:1 adduct of dianion and zwitterion also displays proton transfer and Coulomb explosion into the mono-protonated disulfonic mono-anion and an imidazole-based carbene with sulfonate mono-anion. © 2012 the Owner Societies.